2009
DOI: 10.1089/scd.2007.0266
|View full text |Cite
|
Sign up to set email alerts
|

Teratoma Formation by Human Embryonic Stem Cells Is Site Dependent and Enhanced by the Presence of Matrigel

Abstract: When implanted into immunodeficient mice, human embryonic stem cells (hESCs) give rise to teratoma, tumor-like formations containing tissues belonging to all three germ layers. The ability to form teratoma is a sine qua non characteristic of pluripotent stem cells. However, limited data are available regarding the effects of implantation site and the methods employed for implantation on the success rate of teratoma formation. In this study, the rate of teratoma formation in immunodeficient mice was site depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
176
2
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 234 publications
(186 citation statements)
references
References 25 publications
6
176
2
2
Order By: Relevance
“…Tumor formation in the lung and thymus had the highest probability of teratoma formation while the pancreas was partially siteprivileged [Shih et al, 2007]. More recently, Prokhorova et al, 2008] also demonstrated that the rate of teratoma formation with hESCs in immunodeficient mice was site-dependent (subcutaneous 25-100%; intratesticular 60%; intramuscular 12.5%; and under the kidney capsule 100%).…”
Section: Immunorejectionmentioning
confidence: 97%
“…Tumor formation in the lung and thymus had the highest probability of teratoma formation while the pancreas was partially siteprivileged [Shih et al, 2007]. More recently, Prokhorova et al, 2008] also demonstrated that the rate of teratoma formation with hESCs in immunodeficient mice was site-dependent (subcutaneous 25-100%; intratesticular 60%; intramuscular 12.5%; and under the kidney capsule 100%).…”
Section: Immunorejectionmentioning
confidence: 97%
“…The hESC lines: Harvard HUES-9 (34) (kindly provided by Dr D Melton) and in-house hESC line KMEB2 (35) were maintained undifferentiated using g-irradiated (266.7 rads/min for 15 minutes) primary mouse embryonic fibroblast feeder cells seeded at 20,000 cells/cm 2 in plates (NUNC, Roskilde, Denmark) precoated with gelatin (0.1%) (G1393, Sigma, St. Louis, MO, USA). Undifferentiated hESCs were cultured with KO-Medium (KO-DMEM, 85%; 10829-018, Invitrogen, Taastrup, Denmark) supplemented with knockout serum replacement (KO-SR, 15%; 10828-028, Invitrogen), Glutamax (1%; 35050-038, Invitrogen), MEM nonessential amino acids (1%; 11140-035, Invitrogen), bmercaptoethanol (0.1 mM; M7522, Sigma-Aldrich, Brondby, Denmark), penicillin/streptomycin [5000 U/mL (5000 mg/mL), 15070, Invitrogen], human serum albumin (0.5%, SSI, 8409), and basic fibroblast growth factor (bFGF, 5 ng/mL; 13256-029, Invitrogen).…”
Section: Cell Culturementioning
confidence: 99%
“…Thus, the 10 -20% failure rate of teratoma formation reported by Zhao et al (9) and Araki et al (10) may have been due to insufficient vascularization or cell-cell contact rather than rejection per se. This is supported by the fact that all three studies reported T cell infiltration into teratomas after establishment, but only the two that transplanted subcutaneously reported Ͻ100% teratoma formation, as well in previous work (18). Of course, these teratoma experiments do not reflect the path of clinical translation, which will involve transplantation of cell types differentiated in vitro from iPSCs.…”
Section: Evidence For Autologous Ipsc Immunogenicitymentioning
confidence: 59%